Knowledge of Hormonal Contraception Among Young Women in Poland - Paprocka, Renata; Binder, Julita; Weber-Rajek, Magdalena (Journal of Education, Health and Sport, 2018)
Introduction. Hormonal contraception could activate wide range of biological effects in women body and what’s important these pharmaceuticals are often used for long time. The aim of this study was to examine the level of knowledge among young women studying on the universities of Bydgoszcz (Poland) about the health effects of hormonal contraception. Materials and Methods. 172 women aged from 18 to over 25 years (the majority of respondents were in the age 21-24 years) were assessed with original anonymous questionnaire. Results. The state of knowledge of young women concerning negative aspects of using contraception differs depending on field of study. The awareness of women using contraception was higher than women which didn’t use hormonal contraception. Conclusion. General state of knowledge of studied women concerning using hormonal contraception was not satisfactory. Especially alarming is ignorance of health threads connected with using hormonal contraception among women using this method of contraception.